Varied radiographic appearences of complex odontoma - Case series and clinical-radiographic review - Gargi, Vidisha; SM, Ravi Prakash; K, Nagaraju (Journal of Oral Diagnosis, 2018)
Odontome is most common benign odontogenic tumour. Radiographically and histologiclly it is characterized by production of mature enamel, dentin, cementum and pulp tissue. The structural relationship vary from nondescript mass of dental tissue referred to as complex odontome and multiple well-formed teeth (denticles) known as compound odontome. Odontomes are often found during routine radiographic investigations and are the most common cause of delayed eruption of the permanent teeth and sometimes it may itself erupt in the oral cavity. We are presenting a case series of complex odontomes with varied clinical features and radiographic appearances which may be helpful for the clinician to achieve accurate diagnosis in order to avoid subsequent complications.